The Effectiveness of The Problem-Based Learning Model Assisted by Interactive Videos on Critical Thinking Skills - Romadhoni, Siti Dzakiya; Hakim, Fachri; Ningrum, Lis Setiyo (Universitas Negeri Gorontalo, 2025)
The 21st century demands that students develop various skills, including critical thinking. This study investigates how effective an interactive video-assisted Problem-Based Learning (PBL) model is in enhancing students' critical thinking skills on the topic of atomic structure and the benefits of nanomaterials. The research used a quasi-experimental design with non-equivalent control groups. The sample was selected using cluster random sampling, with class X4 as the experimental group and class X6 as the control group. Data were collected through pre-tests and post-tests, which were analyzed using the product-moment correlation formula to validate the test instruments. The results showed that the experimental group's average post-test score for critical thinking skills was 75.944, higher than the control group's score of 61.278. The hypothesis test using an independent sample t-test revealed a Sig (2-tailed) value of 0.000, which is less than 0.05, indicating that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. Additionally, the effectiveness of the model was assessed using the n-gain test, resulting in a mean value of 0.6327, which falls into the medium effectiveness category.